Constitutional secularism in an age of religious revival - Mancini, Susanna; Rosenfeld, Michel, 1948- (Oxford, United Kingdom : Oxford University Press, 2014)
'The revival of religion in many parts of the world and the migration of religious cultures as part of the process of globalization have posed a serious challenge to traditional constitutional secularism. This challenge comes in the form of a political and institutional struggle against secular constitutionalism, and a two pronged assault on the very legitimacy and viability of the concept. On the one hand, constitutional secularism has been attacked as inherently hostile rather than neutral toward religion; and, on the other hand, constitutional secularism has been criticized as inevitably favouring one religion (or set of religions) over others'--
Introduction / Susanna Mancini and Michel Rosenfeld -- Conflicts between general laws and religious norms / Dieter Grimm -- The context of secularism : a critical appraisal of the post-secular argument / Nadia Urbinati -- The myth of the neutral state and the individualization of religion : the relationship between state and religion in the face of fundamentalism / Karl-Heinz Ladeur -- Preliminaries to a concept of constitutional secularism / Andras Sajo -- Recasting secularism as one conception of the good among many in a post-secular constitutional polity / Michel Rosenfeld -- The tempting of Europe, the political seduction of the Cross : a Schmittian reading of Christianity and Islam in European constitutionalism / Susanna Mancini -- On the secularization of the public square : Jews in France and in the United States / Pierre Birnbaum -- Sovereignty and laicite / Michel Troper -- Egypt's new Constitution : the Islamist difference / Lama Abu-Odeh -- The constitutional boundaries of religious accommodation / Ran Hirschl and Ayelet Shachar -- Headscarf versus burqa : two French bans with different meanings / Patrick Weil -- Veiling and women's intelligibility / John Borneman -- Reproductive rights in a Jewish and democratic state / Daphne Barak-Erez -- One among many? The Catholic Church between universalism and pluralism / Gustavo Zagrebelsky -- Religious marriage in a liberal state / Gidi Sapir and Daniel Statman -- Are secularism and neutrality attractive to religious minorities? : Islamic discussions of Western secularism in the'jurisprudence of Muslim minorities' (Fiqh Al-Aqalliyyat) discourse / Andrew F. March -- The ultra-orthodox community in Israel and the right to an exclusively religious education / Gila Stopler -- Religion and freedom of speech : portraits of Muhammad / Robert Post.
Includes bibliographical references and index.
Keywords: Religion and state; Religion and law; Constitutional law -- Religious aspects; Secularism -- Political aspects